Analysis Of The Benefits Of Social Media As A Medium Global Marketing In Increasing Product Sales Revenue - Suhairi; Farhan Edma Manurung; Preti Intan Sari; Syakya Maulida (CV. AFDIFAL MAJU BERKAH, 2023)
The use of the internet in Indonesia is very high, so that Youtube is able to occupy the highest position of being the most popular, then the ranking is for users of Facebook, Instagram, Twitter, WhatsApp and Google. With age categories from various groups who have active characters in social media and using the internet. The approach used in this study is to use a literature review approach. In collecting data, the authors collect data and information related to digital marketing and marketing systems through supporting data sourced from research journals, both national and international, supporting books, letters newspapers and magazines. This study aims to find out how social media is utilized as a global marketing medium. The results of this study are that the potential for marketing in the modern era is dominated by marketing through social media which is accessed through personal devices. In conclusion, there are many uses of social media today to boost business that have been discussed in this study. Social media connects people around the world where they can keep in touch and share their experiences. This is made possible by the digital ecosystem.